Impact of measuring quantification of blood loss versus estimation of blood loss during cesarean deliveries. Issue 2 (27th July 2022) - Bhatt, Akshay; Hughes‐Hogan, Logan; Mitchell, Takiyah; Nair, Singh; Chuang, Meleen; Chen, Steven L.; Reddy, Shamantha
Abstract: Objective: Our objective was to determine whether there is a numerical difference between quantitative blood loss (QBL) versus visual estimation of blood loss (EBL) during cesarean delivery (CD), and whether initiation of QBL leads to increased recognition and intervention for postpartum hemorrhage. Methods: A retrospective review was conducted of 250 patients undergoing CD with only EBL documented and 250 patients undergoing CD with both EBL and QBL documented at Montefiore Medical Center between October 2017 and November 2018. Since May 2018, the protocol for all CD included documentation of EBL and QBL. Results: Average EBL when documented alone (897.0 ml ± 301.0 ml) trended lower than average EBL when documented with QBL (940.0 ml ± 371.0 ml, P  = 0.161). For CD with both blood loss documented, average EBL (940.0 ml ± 371.0 ml) was significantly lower than average QBL (1065.3 ml ± 649.8 ml, P  = 0.0001). CD with both blood loss documented had a greater number of blood transfusions (24 CD, 9.6%) versus only EBL documented (14 CD, 5.6%) ( P  = 0.125). Conclusion: The use of QBL may function in the algorithm to determine up‐front resuscitative intervention to improve maternal outcomes and merits further study. Synopsis: Quantitative blood loss measurement is associated with higher documented estimated blood loss, greater frequency of blood transfusion, and improved detection of postpartum hemorrhage.